Woman Education Texts from Surakarta and Yogyakarta Palace - Nugroho, Yusro Edy; Supriyanto, Teguh; Rokhman, Fathur; Mardikantoro, Hari Bakti (International Journal of Psychosocial Rehabilitation, 2020)
The Javanese Palace was a big community of Islamic Mataram dynasty where teaching texts for Javanese women in the 19th century AD have developed. Several texts regarding the education for Javanese women are currently recorded as historical documents that can serve as references or materials to reveal the background of their paradigm and behavior in the present day. This study focused on the inventory efforts of Javanese manuscripts about teaching for women sourced from texts produced in Surakarta Sunanate, Yogyakarta Sultanate, Mangkunegaran Duchy, and Pakualaman Duchy. However, this study did not only attempt to look for the origin of the texts and publish their editions but also resulted in the distribution portrait of the manuscripts that contained woman education in the form of serat piwulang. A philological approach was employed in this study, in which the data collection technique involved the catalog study. The collected data were manuscripts of piwulang (teaching) for women sourced from some libraries in Indonesia, namely Sonobudoyo library in Yogyakarta, Faculty of Letters library of Universitas Indonesia, Yogyakarta Language Center library, and National Library of Indonesia in Jakarta. The results of this study were manuscripts regarding woman education in the 19th century spread over several libraries in Indonesia. Those also included manuscript collections owned by four Javanese Palaces, including Surakarta Sunanate, Yogyakarta Sultanate, Mangkunegaran Duchy, and Pura Pakualaman Duchy. Many serat piwulang texts comprising teaching for women included Serat Wulang Putri Nyi Adisara, Serat Darmaduhita, Serat Darmarini, Serat Warayagnya, Serat Menak Cina, Serat Panji Jayengsari, Serat Candrarini, Serat Wulang Estri PB IX, Serat Wulang Wanita, and Piwulang Putra-Putri Bab Palakrama. These manuscripts used to be copied and distributed to married princesses who lived in other places. The marriage of the princesses was usually related to politics for establishing a harmonious relationship among authorities in the hierarchy of in-laws and son/daughter-in-law, vice versa.